2015
DOI: 10.1007/s00417-015-2967-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of rhinostomy shape and surgical outcome after endoscopic endonasal dacryocystorhinostomy

Abstract: The incidence rate of symptomatic epiphora after EDCR was approximately 12 %, and this result may have been associated with cavernous and concealed rhinostomy shapes. For patients with persistent epiphora and anatomically patent DCR, it is important to identify rhinostomy shape by endoscopy in order to differentiate causes of functional failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…Previous studies have suggested that various factors such as the extent of bone removal, rhinostomy location and nasal packing material might be associated with the physiology of rhinostomy shape formation . However, our study suggests that characteristics of the lacrimal sac itself may play a more prominent role in determining the rhinostomy shape.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…Previous studies have suggested that various factors such as the extent of bone removal, rhinostomy location and nasal packing material might be associated with the physiology of rhinostomy shape formation . However, our study suggests that characteristics of the lacrimal sac itself may play a more prominent role in determining the rhinostomy shape.…”
Section: Discussioncontrasting
confidence: 63%
“…The following intraoperative variables were defined and evaluated: (i) the width of the nasal cavity (narrow/wide), with a narrow cavity defined as either the inability of two 7‐French suction tips (about 5 mm diameter) to pass through or the ability to barely pass through the space between the nasal septum and the lateral nasal wall after nasal mucosal shrinkage, (ii) the amount of bleeding (minimal or significant), with significant bleeding defined as bleeding of sufficient quantity to obstruct the surgeon's view and increase the difficulty of the surgery, (iii) the rhinostomy location (anterior/posterior), with an anterior rhinostomy defined as the lacrimal sac located anterior to the axilla of the middle turbinate, (iv) the size of the initial ostium (mm), calculated based on the maximal vertical height of the bony ostium using a 5‐mm suction tip or a 0.9‐mm size 1 Bowman probe as a guide, (v) the presence of chronic dacryocystitis, defined as whether milky or mucopurulent discharge was expressed from the lacrimal sac opening, (vi) lacrimal sac size (small/large), with a small lacrimal sac defined as a vertical sac cavity height <8 mm . The lacrimal sac thickness and mobility which had not been previously analysed were therefore subjectively assessed, (vii) lacrimal sac thickness (thin/thick), with a thin sac wall defined as <0.9 mm using a size 1 Bowman probe, (viii) sac mobility (good/poor), with poor sac mobility defined as poor posterior reflection of the posterior lacrimal sac flap after sac opening …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The shape of DCR ostium depends on the size, location and the characteristics of soft tissue and bony openings. Recent studies showed correlation of ostium shape and functional outcome after endoscopic DCR 20 . Similarly, we found that better-shaped (deep and wide-open) ostium was significantly associated with functional success (odds ratio 2.16, p = 0.03) in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%